A SPIRITUAL PATH OF A GRAVE DIGGER - Afandi, Nur Aziz (Teosofia: Indonesian Journal of Islamic Mysticism, 2018)
Heart (qalb) has a higher function than do other sensory organs such as eyes and ears have because heart is the executing part of the soul that changes human spiritual potentiality into actuality (Ansari, 2003). Spiritual actuality of heart such as mukasyafah is possible when it has achieved cleanliness and clarity. Sufism as a spiritual path offers several steps to clean and purify heart. This study explores the spiritual path that has been experienced by a grave digger in the form of mukasyafah towards the sound of complaints and pain from a grave. The data of this essay was gained from interviews with a grave digger in Kediri, East Java. This study concludes that the spiritual path traversed by the grave digger is, among other things, the path of heart which is exercised by the subject by giving help, alleviating sufferings of others, praying for the deceased, and being gentle towards his fellow people. The path of reason is passed by the subject by doing what he obtained from his studying Islam. The path of group is done by having good relations with others. While the path of service is carried out by the subject by giving emphaty to other people who are experiencing distress, giving hands to those who ask for help and giving alms to those in need. The way of dhikr is done by always remembering Allah, realizing and believing in Allah as the provider of the provision and who regulates one's sustenance and being honest in work expecting God’s blessing.